Microwave coupler for W‐band micro re‐entrant square cavities. Issue 7 (1st May 2016) - Paoloni, Claudio; Mineo, Mauro; Yin, Huabi; Zhang, Liang; He, Wenlong; Robertson, Craig W.; Ronald, Kevin; Phelps, Alan D.R.; Cross, Adrian W.
Abstract : Klystrons are vacuum electronic devices widely used for microwave amplification up to the millimetre‐wave region. The opportunity to push the operating frequency of conventional klystrons above 30–40 GHz is limited by the fabrication difficulties of the cavities that have very small dimensions. A high order mode micro re‐entrant square cavity was purposely devised to be compatible with the available micro fabrication processes and represents a viable solution for the design of millimetre‐wave klystrons. In this study, a coupler to correctly excite the higher order mode of the square re‐entrant cavities for W‐band operation is proposed. The design of the proposed novel coupler structure has been validated by realisation and measurement of a scaled X‐band prototype. The post‐realisation tuning methods adopted to improve the matching of the high order mode are also presented.